2012
DOI: 10.1002/14651858.cd003811.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics to prevent complications following tooth extractions

Abstract: Although general dentists perform dental extractions because of severe dental caries or periodontal infection, there were no trials identified which evaluated the role of antibiotic prophylaxis in this group of patients in this setting. All of the trials included in this review included healthy patients undergoing extraction of impacted third molars, often performed by oral surgeons. There is evidence that prophylactic antibiotics reduce the risk of infection, dry socket and pain following third molar extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(82 citation statements)
references
References 74 publications
0
69
0
13
Order By: Relevance
“…Aunque se cree que su uso podría prevenir la aparición de infecciones y de alveolitis seca, diversos autores reportan que no es necesario el uso de antibióticos como profilácticos 2,8,46,47 . Su uso no está recomendado a menos que el paciente esté inmunocomprometido o si existiera el riesgo de desarrollar osteomielitis 8,47 .…”
Section: Antibióticosunclassified
“…Aunque se cree que su uso podría prevenir la aparición de infecciones y de alveolitis seca, diversos autores reportan que no es necesario el uso de antibióticos como profilácticos 2,8,46,47 . Su uso no está recomendado a menos que el paciente esté inmunocomprometido o si existiera el riesgo de desarrollar osteomielitis 8,47 .…”
Section: Antibióticosunclassified
“…Our results in a VA clinic identified that while 87.3% of antibiotics were indicated, 91.8% of antibiotics prescribed for infection prophylaxis were inconsistent with recommendations. In our study, postprocedure antibiotic prophylaxis was administered for the majority of patients undergoing tooth extraction or implant surgery despite evidence supporting administering antibiotics preprocedure only [8, 13, 17, 18]. Postprocedure antibiotics used in this setting were prescribed for an extended duration (mean, 7.2 days for an excess of 824 days in the cohort), for which evidence is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, national guidelines for dental procedure antibiotic prophylaxis are lacking in the absence of comorbidities (ie, cardiac conditions, prosthetic joints). However, a systematic review by the Cochrane Collaboration on the use of antibiotics for infection prophylaxis following tooth extractions found that antibiotics reduced the risk of infection, but also increased the risk of adverse events [17]. The authors concluded that due to the risk of adverse events and resistant bacteria, clinicians should carefully consider treating healthy patients with postprocedural prophylactic antibiotics [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations